Zambia : 2005 Article IV Consultation, Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver and Modification of Performance Criterion, and Financing Assurances Review; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report, 2006)
Zambia's 2005 Article IV Consultation and Third Review Under the Poverty Reduction and Growth Facility are discussed. Expenditure restraint, including on the wage bill, has helped to put the fiscal operations of the government on a sustainable course and contributed to the attainment of the Heavily Indebted Poor Countries completion point. Progress has also been made on the structural reforms agenda, including public expenditure management, public debt management, the resolution of insolvent nonbank financial institutions, and the privatization of the Zambia National Commercial Bank.